The Pyhäntaka formation, Southern Finland: A sequence of metasandstones and metavolcanic rocks upon an intra-orogenic unconformity - M. Nironen (Bulletin of the Geological Society of Finland, 2011)
Detrital zircon studies suggest that the few quartzite occurrences in southern Finland are younger than 1.87 Ga and express sedimentation after 1.89–1.87 Ga accretional deformation and metamorphism in the Svecofennian orogenic belt. Detailed field work in the high-grade metamorphic Pyhäntaka area allowed to distinguish an overturned formation within metagraywackes (cordierite paragneisses) and psammites. The Pyhäntaka formation has a maximum thickness of 1000 meters and consists of quartzite overlain by meta-arkose, metatuff, and metabasalt on top. An uncorformity, expressed by a weathering surface, separates the quartzite from underlying metagraywacke. The metavolcanic rocks within, stratigraphically underlying and overlying the Pyhäntaka formation are mostly basalts and basaltic andesites, but a felsic volcanic rock and dacitic fragments in volcaniclastic rocks imply bimodal affinity. The quartzite was deposited during a stable intra-orogenic period probably after accretion but before 1.83–1.80 Ga collisional deformation and metamorphism in the Svecofennian orogen. Rifting during the intra-orogenic period and accumulation of variable material in the rift from nearby sources by fluvial processes is a viable scenario for deposition and preservation of the Pyhäntaka formation. Geochemical diagrams of the metavolcanic rocks show a scatter that is best explained by source heterogeneity and crustal contamination. Despite their (likely) post-accretion setting the basaltic rocks show arc-type characteristics due to subduction-modified lithospheric mantle sources. Because of recycling, also the paragneisses in the Pyhäntaka area are geochemically similar in spite that they represent different tectonic settings. The use of elemental geochemistry alone appears to be insufficient for discriminating tectonic settings of basalts or graywackes in the Svecofennian of southern Finland where accretion and post-accretion settings were largely obliterated by late collision.